Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

Early Depression Detection with Transformer Models: Analyzing the Relationship between Linguistic and Psychology-Based Features - Halimeh, Haya; Caron, Matthew; Müller, Oliver (Hawaii International Conference on System Sciences)
Clinical depression is a serious mental disorder that poses challenges for both personal and public health. Millions of people struggle with depression each year, but for many, the disorder goes undiagnosed or untreated. Over the last decade, early depression detection on social media emerged as an interdisciplinary research field. However, there is still a gap in detecting hesitant, depression-susceptible individuals with minimal direct depressive signals at an early stage. We, therefore, take up this open point and leverage posts from Reddit to fill the addressed gap. Our results demonstrate the potential of contemporary Transformer architectures in yielding promising predictive capabilities for mental health research. Furthermore, we investigate the model’s interpretability using a surrogate and a topic modeling approach. Based on our findings, we consider this work as a further step towards developing a better understanding of mental eHealth and hope that our results can support the development of future technologies.
Keywords: Social Media and Healthcare Technology; early depression detection; liwc; mental health; transfer learning; transformer architectures

Workarounds as generative mechanisms for bottom‐up process innovation—Insights from a multiple case study - Bartelheimer, Christian; Wolf, Verena; Beverungen, Daniel (Information Systems Journal)
Abstract Workarounds are goal‐driven deviations from the standard operating procedures performed to overcome obstacles constraining day‐to‐day work. Despite starting as temporary fixes, they can become established across an organisation and trigger the innovation of processes and IT artefacts that can resolve misfits permanently. Although prior research has elicited antecedents and types of workarounds, it is not known how workarounds diffuse in an organisation and, thereby, innovating co‐workers' activities, IT artefacts, and organisational structures. The results of our multiple two‐year case study provide unique empirical insights into the diffusion of workarounds and how they can act as generative mechanisms for bottom‐up process innovation.
Keywords: Computer Networks and Communications; Information Systems; Software

Preservice teachers’ mathematics-related values and expectancy in the transition from school to university
Many preservice mathematics teachers lose their motivation during their first year at university. This phenomenon has been repeatedly described in recent years but is not yet fully understood. Since motivation may relate to different objects such as mathematics or teaching, we aim to qualitatively reconstruct different facets of the central motivational constructs of Situated-Expectancy-Value theory (intrinsic value, attainment value, utility value, cost, and expectancy of success) for preservice mathematics teachers. The analysis of longitudinal group interviews of 14 preservice higher-secondary mathematic teachers from a German university revealed different objects of motivation (e.g., teaching mathematics, scientific mathematics, procedural mathematics, or proof-based mathematics) in preservice teachers' values and expectancy of success. Furthermore, relations between those values and expectancy of success were identified that played a significant role in preservice teachers’ motivational development over their first semester (e.g., relations of attainment value for scientific mathematics and psychological cost). Theoretical and practical implications towards a teaching-specific conceptualization of expectancy of success and values and value interventions are being discussed.

Microinverter testing update using high power modules: Efficiency, yield, and conformity to a new ”estimation formula” for variation of PV panel size - Krauter, Stefan; Bendfeld, Jörg; Möller, Marius Claus (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
The market for microinverters is growing, especially in Europe. Driven by the strongly rising prices for electricity, many small photovoltaic energy systems are being installed. Since monitoring for these plants is often quite costly, their yields are often not logged. Since 2014, microinverters have been studied at the University of Paderborn. The investigations are divided into indoor and outdoor tests. In the indoor area conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro- and CEC weightings. In the outdoor laboratory, the behavior in the real world is tested. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules. Here, the investigations were carried out with modules of the power of 215 Wp until the year 2020. Because of the increasing module power nowadays, modules with an output of 360 Wp are now being used. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation resulting in the actual yield, any module & inverter configuration can be characterized by just the two coefficients.

Model of a Self-Sufficient PV Home using a Hybrid Storage System based on Li-Ion Batteries and Hydrogen Storage with Waste Heat Utilization - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
This paper provides a hybrid energy system model created in Matlab/Simulink which is based on photovoltaics as its main energy source. The model includes a hybrid energy storage which consists of a short-term lithium-ion battery and hydrogen as long-term storage to ensure autonomy even during periods of low PV production (e.g., in winter). The sectors heat and electricity are coupled by using the waste-heat generated by production and reconversion of hydrogen through an electrolyser respectively a fuel cell. A heat pump has been considered to cover the residual heat demand (for well insulated homes). Within this paper a model of the space heating system as well as the hot water heating system is presented. The model is designed for the simulation and analysis of a whole year energy flow by using a time series of loads, weather and heat profiles as input. Moreover, results of the energy balance within the energy system by simulation of a complete year by varying the orientation (elevation and azimuth) of the PV system and the component sizing, such as the lithium-ion battery capacity, are presented. It turned out that a high amount of heating energy can be saved by using the waste heat generated by the electrolyser and the fuel cell. The model is well suited for the analysis of the effects of different component dimensionings in a hydrogen-based energy system via the overall energy balance within the residential sector.

Hybrid Energy System Model in Matlab/Simulink based on Solar Energy, Lithium-Ion Battery and Hydrogen - Möller, Marius Claus; Krauter, Stefan (Energies / Special Issue "Sustainable Energy Concepts for Energy Transition")
In this paper, a model of a hybrid, hydrogen-based energy system for a household which includes the heating sector is presended. With such an energy system it's possible to enable energy autarky over a whole year based on solar energy. The scope of this study was to present a verified hybrid energy system model created in Simulink which can be used to prospectively size future similar energy systems where hydrogen in combination with a li-ion battery shall be used as energy storage type.

Obesogenic eating behaviour and dietary intake in German children and adolescents: results from the GINIplus and LISA birth cohort studies - Marb, Anne; Libuda, Lars; Standl, Marie; Koletzko, Sibylle; Bauer, Carl-Peter; Schikowski, Tamara; Berdel, Dietrich; von Berg, Andrea; Herberth, Gunda; Bühlmeier, Judith; Harris, Carla P. (European Journal of Clinical Nutrition)
Abstract Background/objectives The transition to adolescence is characterised by considerable behavioural changes, including diet. This study describes the level of obesogenic eating behaviours in 10- and 15-year-olds, and their association with dietary intake. Subjects/methods Participants of the 10- and 15-year follow-ups of the German GINIplus and LISA birth cohort studies were included (N 10 = 2257; N 15 = 1880). Eating behaviours and dietary intake were assessed via self-report questionnaires. Sex-stratified, cross-sectional associations of “external eating”, “emotional eating” and “dietary restraint” (the latter at age 15 years only) with dietary intake (17 food groups—categorised into tertiles, macronutrients, and total energy) were assessed using multinomial logistic or multiple linear regression as required, adjusting for covariates and correcting for multiple testing. Results Reported levels of eating behaviours were low in both age-groups. External eating was higher in 10-year-old males than females, while all eating behaviours were most pronounced in 15-year-old females. At 10 years, emotional eating was associated with medium vegetable intake in females (Relative Risk Ratio (RRR) = 1.84, p = 0.0017). At 15 years, external eating was associated with total energy (kJ) in females ( β = 718, p = 0.0002) and high butter intake in males (RRR = 1.96, p = 0.0019). Dietary restraint in females was inversely associated with total energy ( β = −967, p < 0.0001) and omega-3 fatty acids (Means Ratio (MR) = 0.94, p = 0.0017), and positively associated with high fruit (RRR = 2.20, p = 0.0003) and whole grains (RRR = 1.94, p = 0.0013). Conclusion Obesogenic eating behaviour scores are low among children and adolescents of a predominantly high socioeconomic status population and present only few associations with specific aspects of diet, mainly among adolescent females.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Das Belastungserleben von Lehramtsanwärterinnen und -anwärtern im Vorbereitungsdienst - Bruns, Marike; Caruso, Carina; Ackermann, Luisa (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Die Ausbildung von Lehrkräften teilt sich in Studium und Vorbereitungsdienst. Während im Studium Wissen grundgelegt wird, dient der Vorbereitungsdienst, der überwiegend in der Schule stattfindet, dem Erwerb praktischer Kompetenzen, was den Rückbezug auf theoretisch fundierte Kenntnisse und den Aufbau erfahrungsbasierten Wissens umfasst. Die Maßnahmen zur Eindämmung der Corona-Pandemie verändern nicht nur den Schulalltag, sondern haben auch Einfluss auf die Kompetenzentwicklung angehender Lehrkräfte im Vorbereitungsdienst, die ihre Berufsausbildung unter veränderten Rahmenbedingungen durchführen müssen. Die aktuellen Rahmenbedingungen können u. a. aufgrund fehlender bzw. eingeschränkter Praxiserfahrungen eine reguläre Ausbildung erschweren, was zu einem erhöhten Belastungsempfinden der angehenden Lehrkräfte beitragen kann. In diesem Beitrag wird Bezug genommen auf Daten einer explorativen Interviewstudie mit Lehramtsanwärterinnen und -anwärtern aus Nordrhein-Westfalen (N = 19), die während der Pandemie im Jahr 2020 ihren Vorbereitungsdienst absolviert haben. Es wird dabei den Fragen nachgegangen, welche Belastungsfaktoren im Zusammenhang mit der Corona-Pandemie während des Vorbereitungsdienstes auftreten können und inwieweit sich angehende Lehrkräfte während ihres Vorbereitungsdienstes vor dem Hintergrund der aktuellen Rahmenbedingungen infolge der Corona-Pandemie als belastet erleben.
Keywords: Corona-Pandemie; Lehramtsanwärter:innen; Lehrer:innenausbildung; Professionalisierung; Vorbereitungsdienst / corona pandemic; prospective teachers; teacher training; professionalization; preparatory service

Comparing Student high and low Reading Performance with Differentiated Digital Reading Materials - Paleczek, Lisa; Ender, Daniela; Kogler, Andrea; Seifert, Susanne (European Conference on e-Learning)
The present study investigates eight Grade-4 classes (9- to 12-year-olds, 52.1% girls) who worked on at least 10 lessons using project RegioDiff material. The study focuses on one of these lessons (including nine text passages and corresponding tasks) and on students with low (19 students, percentile <15) and high reading skills (29 students, percentile > 70). While students were working with the material, screencasts were recorded (30h). The construct “task performance” (processing time, response accuracy, and task engagement) was then analysed using the screencasts.
The analysis revealed that the two groups differed significantly in the processing time of two tasks, but not in the total time spent on all nine tasks. Significant differences were revealed also for general task engagement. Task engagement was highly correlated with processing time. Participants with higher reading skills spent more time on the tasks and were more engaged than participants with lower reading skills. However, we did not find any differences in terms of answer accuracy. This indicates that task difficulty and student reading skills were well matched.
The study also shows how tasks may be adapted or augmented in order to match the learning environment more closely to student learning needs.

First-year university students' self-regulated learning during the COVID-19 pandemic: a qualitative longitudinal study - Liebendörfer, Michael; Kempen, Leander; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract When the COVID-19 pandemic began, many universities switched to fully online teaching. This unexpected switching to online teaching was challenging for both teachers and students, and restrictions that were put in place because of pandemic made this challenge even greater. However, new ways of teaching might also open new opportunities for students’ learning. The research question driving our study was as follows: how do students regulate their learning and specifically their choice of resources and peer learning in university mathematics classes that are fully taught online as offered during the COVID-19 pandemic? We report on a longitudinal, qualitative study in which students recorded a brief audio diary twice a week over one whole semester (14 weeks). We focused on three students who completed 70 interviews in total and finished the semester with varying degrees of success. The results show how the students structured their studying (e.g., the roles that deadlines or synchronous teaching events played). They illustrate the strengths and limitations of digital materials provided by the lecturer and the use of complementary media. Further, the pandemic uncovered the double-edged role of simple, often anonymous exchanges (e.g., via Discord servers), with few binding forces for either side, and the significance of stable learning partnerships for students’ success. Our research highlights aspects that should be focal points when comparing traditional instruction and online instruction during the pandemic from a self-regulatory perspective. Practical implications refer to how these aspects can be combined sensibly in fully online courses, but also in blended learning contexts.
Keywords: General Mathematics; Education

Developmental Paths of Pointing for Various Motives in Infants with and without Language Delay - Rohlfing, Katharina J.; Lüke, Carina; Liszkowski, Ulf; Ritterfeld, Ute; Grimminger, Angela (International Journal of Environmental Research and Public Health)
Pointing is one of the first conventional means of communication and infants have various motives for engaging in it such as imperative, declarative, or informative. Little is known about the developmental paths of producing and understanding these different motives. In our longitudinal study (N = 58) during the second year of life, we experimentally elicited infants’ pointing production and comprehension in various settings and under pragmatically valid conditions. We followed two steps in our analyses and assessed the occurrence of canonical index-finger pointing for different motives and the engagement in an ongoing interaction in pursuit of a joint goal revealed by frequency and multimodal utterances. For understanding the developmental paths, we compared two groups: typically developing infants (TD) and infants who have been assessed as having delayed language development (LD). Results showed that the developmental paths differed according to the various motives. When comparing the two groups, for all motives, LD infants produced index-finger pointing 2 months later than TD infants. For the engagement, although the pattern was less consistent across settings, the frequency of pointing was comparable in both groups, but infants with LD used less canonical forms of pointing and made fewer multimodal contributions than TD children.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Scaffolding Close Reading of Mathematical Text in Pre-service Primary Teacher Education at the Tertiary Level: Design and Evaluation - Rezat, Sebastian; Malik, Sara Naseem; Leifeld, Markus (International Journal of Science and Mathematics Education)
Abstract Even in the digital age, learning mathematics at an academic level still requires much reading of mathematical text. Research has shown that reading mathematical text requires readers to engage with all the structures of the book and with its pedagogical voice, making connections, and plausible reasoning. Specific practices and strategies that support the close reading of mathematical text have been suggested; however, descriptions and empirical evaluations of materials designed to support these activities are rare. We present the design and first evaluation cycle of materials developed in a design research project that aims to scaffold close reading of mathematical text. The materials were designed and evaluated in a German university course on elementary geometry for first-year teacher education students who study mathematics to become primary teachers. The reading strategies were explained and modeled for students in reading-strategy videos. Additionally, close reading of mathematical text was scaffolded by close-reading tasks and homework tasks and problems that build on the reading strategies and were specifically designed to foster understanding of the mathematical text. Survey data were collected from 296 students to evaluate their use of and attitude toward the different materials. The quantitative results indicate that students used the materials and were generally able to learn the course content by themselves. From all provided materials, they found the close-reading tasks most helpful. A qualitative analysis of answers to open questions revealed issues with different materials, particularly with the script, and requests for additional materials. The issues with the script were categorized inductively. The categories are presented as a qualitative result of the study and discussed.
Keywords: General Mathematics; Education

Should I Stay or Should I Go? Discussing the Advantages and Disadvantages of Taking a Gap Year - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Rapid amelioration of anorexia nervosa in a male adolescent during metreleptin treatment including recovery from hypogonadotropic hypogonadism - Antel, Jochen; Tan, Susanne; Grabler, Marvin; Ludwig, Christine; Lohkemper, Dominik; Brandenburg, Tim; Barth, Nikolaus; Hinney, Anke; Libuda, Lars; Remy, Miriam; Milos, Gabriella; Hebebrand, Johannes (European Child & Adolescent Psychiatry)
Abstract With this case report we support our medical hypothesis that metreleptin treatment ameliorates starvation related emotional, cognitive and behavioral symptomatology of anorexia nervosa (AN) and show for the first time strong effects in a male patient with AN. A 15.9 year old adolescent with severe AN of eight-month duration was treated off-label with metreleptin. Hyperactivity was assessed with accelerometry. Visual analogue scales (VAS), validated self- and clinician rating scales and lab results tracked changes from baseline to end of the 24-day dosing period and a five-month follow-up. Substantial improvements of mood and eating disorder related cognitions and hyperactivity set in after two days of treatment. During dosing, sub-physiological testosterone and TT3 levels normalized; clinically libido reemerged. Weight did not increase substantially during the dosing period. During follow-up target weight was attained; mood did not deteriorate; hyperactivity ceased. The results substantiate the strong effects seen in female cases and underscore the need for a double-blind placebo-controlled trial to confirm the observed strong, multiple and rapid onset beneficial effects of metreleptin in AN.

Spring Forward, Don't Fall Back: The Effect of Daylight Saving Time on Road Safety - Bünnings, Christian; Schiele, Valentin (The Review of Economics and Statistics)
In this paper, we analyze the effect of light conditions on road accidents and estimate the long run consequences of different time regimes for road safety. Identification is based on variation in light conditions induced by differences in sunrise and sunset times across space and time. We estimate that darkness causes annual costs of more than £500 million in Great Britain. By setting daylight saving time year-round 8 percent of these costs could be saved. Thus, focusing solely on the short run costs related to the transition itself underestimates the total costs of the current time regime.

High Incidence of Anterior Cruciate Ligament Injuries Within the First 2 Months of the Season in Amateur Team Ball Sports - Mouton, Caroline; Gokeler, Alli; Urhausen, Anouk; Nührenbörger, Christian; Seil, Romain (Sports Health: A Multidisciplinary Approach)
Background: The incidence of anterior cruciate ligament (ACL) injuries is commonly reported as an annual incidence rate. There is relatively little information about the seasonal aspects of these injuries. The aim of the current study was to analyze the distribution of ACL injuries during the season in nonprofessional soccer, handball, and basketball based on a retrospective analysis of a hospital-based registry. Hypothesis: ACL injuries in soccer, handball, and basketball were more common within the first 2 months of the season in comparison with the rest of the year. Study Design: Case series. Level of Evidence: Level 4. Methods: Injury occurrence during the calendar year was divided into 6 periods of 2 months, with segment 1 (S1) representing the first 2 months of the season. For soccer, S1 corresponded to September and October. The season started 1 month later for handball and basketball, so S1 represented October and November. Chi-square tests were used to analyze the distribution of ACL injuries among segments according to gender, age, sports, and injury mechanism (contact/noncontact). Results: A total of 371 ACL injuries were included (soccer, 258, handball, 56, basketball, 57). Overall, the distribution of ACL injuries was not uniform across the segments ( P < 0.01). Almost one-third of the ACL injuries occurred in S1 (n = 104; 28%). Significant differences could be observed according to sports ( P < 0.01). There were fewer ACL injuries in S2 for soccer compared with basketball ( P < 0.05). In S5, there were significantly more ACL injuries in soccer compared with handball and basketball ( P < 0.05). Conclusion: A high occurrence of ACL injuries was reported immediately within the first 2 months of the season in nonprofessional soccer, handball, and basketball sports. Clinical Relevance: These findings indicate that ACL injury prevention programs should be started in the preseason period to allow for gradual increases of load.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Vitamin D Level Trajectories of Adolescent Patients with Anorexia Nervosa at Inpatient Admission, during Treatment, and at One Year Follow Up: Association with Depressive Symptoms - Föcker, Manuel; Timmesfeld, Nina; Bühlmeier, Judith; Zwanziger, Denise; Führer, Dagmar; Grasemann, Corinna; Ehrlich, Stefan; Egberts, Karin; Fleischhaker, Christian; Wewetzer, Christoph; Wessing, Ida; Seitz, Jochen; et al. (Nutrients)
(1) Background: Evidence has accumulated that patients with anorexia nervosa (AN) are at higher risk for vitamin D deficiency than healthy controls. In epidemiologic studies, low 25(OH) vitamin D (25(OH)D) levels were associated with depression. This study analyzed the relationship between 25(OH)D serum levels in adolescent patients and AN and depressive symptoms over the course of treatment. (2) Methods: 25(OH)D levels and depressive symptoms were analyzed in 93 adolescent (in-)patients with AN from the Anorexia Nervosa Day patient versus Inpatient (ANDI) multicenter trial at clinic admission, discharge, and 1 year follow up. Mixed regression models were used to analyze the relationship between 25(OH)D levels and depressive symptoms assessed by the Beck Depression Inventory (BDI-II). (3) Results: Although mean 25(OH)D levels constantly remained in recommended ranges (≥50 nmol/L) during AN treatment, levels decreased from (in)patient admission to 1 year follow up. Levels of 25(OH)D were neither cross-sectionally, prospectively, nor longitudinally associated with the BDI-II score. (4) Conclusions: This study did not confirm that 25(OH)D levels are associated with depressive symptoms in patients with AN. However, increasing risks of vitamin D deficiency over the course of AN treatment indicate that clinicians should monitor 25(OH)D levels.

Opening up and Sharing Data from Qualitative Research: A Primer - Steinhardt, Isabel; Fischer, Caroline; Heimstädt, Maximilian; Hirsbrunner, Simon David; Ikiz-Akinci, Dilek; Kressin, Lisa; Kretzer, Susanne; Möllenkamp, Andreas; Portzelt, Maike; Rahal, Rima-Maria; Schimmler, Sonja; Wilke, René; et al.
The call for free access to research data and materials is becoming louder and louder from the political and scientific communities in Germany. More and more researchers are facing demands to open up qualitative research data for scientific purposes. They often have a general interest in sharing their data, but are unsure how to proceed. This handout was developed to provide an initial introduction to opening and sharing qualitative data. It was developed at a workshop held in Berlin in January 2020, organized by the research group „Digitization of Science“ of the Weizenbaum Institute, together with its associate researcher Dr. Isabel Steinhardt from the University of Kassel. The workshop involved staff from German research data centers as well as mentees and mentors from the Fellow Program Open Science who already have experience with Open Science, qualitative research, and interdisciplinary research. The handout is addressed primarily to qualitatively researching scientists in Germany. For this reason, it was initially written in German. One year later, we have now decided to translate the handout into English as well. The reasons are twofold: first, we want to make it accessible to researchers in Germany with little knowledge of German. Second, we also want to give interested people outside Germany an insight into the German system and the German discussion about opening up and sharing qualitative data. Due to the objectives and the history of its development, the handout focuses on the German context. This includes the literature references and further sources, and the references to research data centers as well as legal issues. We have deliberately not included a contextualization of the German situation in international discussions in order to keep the handout as short as possible.

Berufsspezifische Reflexionsprozesse durch Einzelfallarbeit im Projekt „Schule für alle": Analyse von zwei Praxisberichten mittels der Dokumentarischen Methode - Reh, Anne; Kottmann, Brigitte; Miller, Susanne (QfI - Qualifizierung für Inklusion)
In dem Beitrag wird ausgehend von der Notwendigkeit einer inklusionspädagogischen Professionalisierung im Lehramtsstudium ein erziehungswissenschaftliches Projekt dargestellt, das es den teilnehmenden Bachelor-Studierenden in besonderer Weise ermöglicht, berufsspezifische Reflexionsprozesse zu durchlaufen. In dem Projekt übernehmen Studierende die einjährige pädagogische Förderung von Grundschulkindern mit bildungsrelevanten Benachteiligungsfaktoren, die häufig von Selektionspraktiken und -maßnahmen bedroht sind. Die Bearbeitung von vorliegenden Common-Sense-Theorien im inklusiven Kontext gilt dabei als ein relevantes Professionalisierungsziel in der Lehramtsausbildung. Konkret werden Ausschnitte aus Praktikumsberichten von zwei Studierenden mittels der dokumentarischen Methode ausgewertet und einander gegenübergestellt, um daran herauszuarbeiten, inwiefern sich die Reflexionen unterscheiden. Es zeigt sich anhand der Analysen, dass im Rahmen der Praxisphase eine Reflection-on-Action und auch die vertiefte Reflexion eigener Common-Sense-Theorien grundsätzlich möglich, jedoch nicht voraussetzungslos ist. Insbesondere kann auch anhand der gewählten Einzelfälle verdeutlicht werden, wie individuell inklusionsbezogene Professionalisierungsprozesse im Rahmen der vorliegenden Praxisphase verlaufen können. Die Analyse offenbart multiple Professionalisierungschancen in Abhängigkeit von den Rahmenbedingungen des Projekts, den individuellen Schwerpunkten der pädagogischen Arbeit oder den individuellen Reflexionen der Studierenden. Abstract Based on the necessity of an inclusive pedagogical professionalisation in the teacher training program, this article presents an educational science project that enables the participating Bachelor students in a unique manner to go through profession-specific reflection processes. In the project, students take on the one-year pedagogical support of primary school children with educational disadvantage factors, who are often threatened by selection practices and measures. In this context, working through present common-sense theories in an inclusive context is considered a relevant professionalization goal in teacher education. Specifically, excerpts from internship reports of two students are analysed by means of the documentary method and compared to each other in order to work out the extent to which the reflections differ. The analyses show that reflection-on-action and in-depth reflection on one's own common-sense theories are generally possible during the practical phase, but not without preconditions. In particular, the selected individual cases can be used to illustrate how individual inclusion-related professionalisation processes can take place within the framework of the present practical phase. The analysis reveals multiple opportunities for professionalisation depending on the general framework of the project, the individual focal points of the pedagogical work or the individual reflections of the students.

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Being a first-year student during COVID-19 pandemic - Büker, Ronja (Zeitschrift für Hochschulentwicklung)

The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.
Keywords: Education

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Debora; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that captures the complexity of countries’ corporate income tax systems faced by multinational corporations. It is based on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries for the year 2016, we find that the level of tax complexity varies considerably across countries, while tax code and framework complexity also vary within countries. From a global perspective, tax complexity is strongly driven by the complexity of both transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different correlation patterns. For example, tax framework complexity is negatively associated with countries’ governance, suggesting that strongly governed countries tend to have less complex tax frameworks, while tax code complexity is positively associated with the statutory tax rate, indicating that high-tax countries tend to have more complex tax codes. However, none of the observed associa-tions are very strong. We conclude that tax complexity represents a distinct country charac-teristic and propose the use of our TCI and its subindices in future research.

CDS investors’ risk perceptions of M&A announcements - Hippert, Benjamin; Uhde, André
We merge a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across North America and Europe with data from 5-year single-name credit default swaps (CDSs) that are written on stock-listed acquiring firms between 2005 and 2018. Subsequently, we empirically analyze the CDS investors’ risk perception of M&A announcements using event study methodologies. As a baseline finding, we provide evidence for significantly positive cumulative average abnormal CDS spread changes suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design as well as regional and sectoral differences. Moreover, results from a large variety of sensitivity analyses including deal and firm characteristics provide a deeper insight into the driving factors of CDS investors’ risk perceptions of M&A announcements.

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Sugar intake among German adolescents: trends from 1990 to 2016 based on biomarker excretion in 24-h urine samples - Perrar, Ines; Gray, Nicola; Kuhnle, Gunter G.; Remer, Thomas; Buyken, Anette; Alexy, Ute (British Journal of Nutrition)
Abstract Trend analyses based on dietary records suggest decreases in the intakes of total sugar (TS), added and free sugar since 2005 among children and adolescents in Germany. In terms of age trends, TS intake decreased with increasing age. However, self-reported sugar intake in epidemiological studies is criticised, as it may be prone to bias due to selective underreporting. Furthermore, adolescents are more susceptible to underreporting than children. We thus analysed time and age trends in urinary fructose excretion (FE), sucrose excretion (SE) and the sum of both (FE + SE) as biomarkers for sugar intake among 8·5–16·5-year-old adolescents. Urinary sugar excretion was measured by UPLC-MS/MS in 997 24-h urine samples collected from 239 boys and 253 girls participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study cohort between 1990 and 2016. Time and age trends of log-transformed FE, SE and FE + SE were analysed using polynomial mixed-effects regression models. Between 1990 and 2016, FE as well as FE + SE decreased (linear time trend: P = 0·0272 and P < 0·0001, respectively). A minor increase in excretion during adolescence was confined to FE (linear age trend: P = 0·0017). The present 24-h excretion measurements support a previously reported dietary record-based decline in sugar intake since 2005. However, the previously seen dietary record-based decrease in TS from childhood to late adolescence was not confirmed by our biomarker analysis, suggesting a constant sugar intake for the period of adolescence.

Younger age and hamstring tendon graft are associated with higher IKDC 2000 and KOOS scores during the first year after ACL reconstruction. - Magnitskaya, N; Mouton, C; Gokeler, A; Nuehrenboerger, C; Pape, D; Seil, R (Knee Surg Sports Traumatol Arthrosc)

Balance task difficulty affects postural sway and cortical activity in healthy adolescents - Gebel, Arnd; Lehmann, Tim; Granacher, Urs (Experimental Brain Research)
Abstract Electroencephalographic (EEG) research indicates changes in adults’ low frequency bands of frontoparietal brain areas executing different balance tasks with increasing postural demands. However, this issue is unsolved for adolescents when performing the same balance task with increasing difficulty. Therefore, we examined the effects of a progressively increasing balance task difficulty on balance performance and brain activity in adolescents. Thirteen healthy adolescents aged 16–17 year performed tests in bipedal upright stance on a balance board with six progressively increasing levels of task difficulty. Postural sway and cortical activity were recorded simultaneously using a pressure sensitive measuring system and EEG. The power spectrum was analyzed for theta (4–7 Hz) and alpha-2 (10–12 Hz) frequency bands in pre-defined frontal, central, and parietal clusters of electrocortical sources. Repeated measures analysis of variance (rmANOVA) showed a significant main effect of task difficulty for postural sway ( p < 0.001; d = 6.36). Concomitantly, the power spectrum changed in frontal, bilateral central, and bilateral parietal clusters. RmANOVAs revealed significant main effects of task difficulty for theta band power in the frontal ( p < 0.001, d = 1.80) and both central clusters (left: p < 0.001, d = 1.49; right: p < 0.001, d = 1.42) as well as for alpha-2 band power in both parietal clusters (left: p < 0.001, d = 1.39; right: p < 0.001, d = 1.05) and in the central right cluster ( p = 0.005, d = 0.92). Increases in theta band power (frontal, central) and decreases in alpha-2 power (central, parietal) with increasing balance task difficulty may reflect increased attentional processes and/or error monitoring as well as increased sensory information processing due to increasing postural demands. In general, our findings are mostly in agreement with studies conducted in adults. Similar to adult studies, our data with adolescents indicated the involvement of frontoparietal brain areas in the regulation of postural control. In addition, we detected that activity of selected brain areas (e.g., bilateral central) changed with increasing postural demands.
Keywords: General Neuroscience

Triggering Demand‒Side‒Management: Correlation of electricity prices, share of renewables, CO2‒contents, and grid‒frequency in the German electricity grid. - Krauter, Stefan; Zhang, L. (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020.)
To provide a simple instrument to operate residential Load-Shifting or Demand-Side-Management systems, the measurement of the actual grid frequency seems to be an appropriate method. Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation. While the specific CO2- emission is decreasing then ‒ due to the increased share of Renewables, the grid frequency is increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side management indicator to lower specific CO2‒emssions and costs (if a dynamic consumption tariff is available). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and a the correlation between grid frequency, power surplus, share of renewables vs. CO2-contents and price at the European energy exchange (EEX) have been calculated. The results show: Correlation between frequency and share of renewables is quite low (r = 0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. There is a good anti-correlation (r = - 0.687) between the EEX‒prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r =0.665), within the one year (2018) that correlation almost doesn’t exist, possibly due to the inflexibility of the bulky lignite power plants that even operate at negative prices.
Keywords: Keywords: Load-Shifting; Demand-Side-Management; DSM; grid frequency; EEX; electricity trading prices; renewable share; flexibility; emissions; CO2

Correlation of grid-frequency, electricity prices, share of Renewables and CO2-contents of German electricity grid to enable inexpensive triggering of Demand-Side-Management - Krauter, Stefan; Zhang, L. (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) 2020)
Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation in the German electricity grid. While the specific CO2-emission is decreasing then - due to the increased share of Renewables, the grid frequency should be increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and -off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side-management indicator to lower specific CO2-emissions and costs (if a dynamic consumption tariff is applied). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and the correlations between grid frequency, share of renewables, CO2-contents, and actual price at the European energy exchange (EEX) have been calculated. The results show: Correlation between grid frequency and the share of renewables is quite low (r=0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. As expected, there is a good anti-correlation (r=-0.687) between the EEX-prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r=0.665), within the one year (2018) that correlation almost doesn't exist, possibly due to the inflexibility of the bulky lignite baseload power plants that even operate at negative prices.
Keywords: CO2; EEX; Grid frequency; DSM; electricity price; Renewable share

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Project “Schule für alle” as a mentoring programme in university teacher education: Professionalization processes of student teachers in different practical university phases - Kottmann, Brigitte; Pieper, Catania (Hungarian Educational Research Journal)
In the mentoring programme project “Schule für alle” (“School for all”) at the University of Bielefeld in North Rhine-Westphalia, university students of primary or special education support a child who is in a situation of crisis for more than one year. In addition, the university students receive ongoing, systematic university support (cf. Kottmann, 2007, p. 32; Kottmann, 2014, p. 380). The accompanying research by “Schule für alle” focuses on the professionalization processes of student teachers during practical phases at universities; accordingly, control groups were included on a pro rata basis. In the pre-post design, all students completed a questionnaire (cf. Pieper, Kottmann & Miller, 2018, p. 294), the evaluation of which shows few changes in the professional perception of competence. Students of the mentoring programme also regularly reflected on their practical experience. Based on the objective hermeneutics it was discovered that the conception of the project supports the process of perceiving, acknowledging and becoming more sensitive in regard to heterogeneous realities in life (cf. Pieper & Kottmann 2019b, p. 312) and that students can consciously perceive and reflect their own normative expectations (cf. Pieper & Kottmann 2019a, p. 79). The article primarily presents the results of the pre-post survey in detail and adds insights into the qualitative evaluation processes. In the conclusion, the potential of the project and mentoring programmes in general, specifically for teacher training students, is described.
Keywords: professionalization of teacher training students; practical university phases; teacher training at universities; men-toring programmes

Age-related efficiency loss of household refrigeration appliances: Development of an approach to measure the degradation of insulation properties - Hueppe, Christian; Geppert, Jasmin; Stamminger, Rainer; Wagner, Hendrik; Hoelscher, Heike; Vrabec, Jadran; Paul, Andreas; Elsner, Andreas; Becker, Wolfgang; Gries, Ulrich; Freiberger, Alfred (Applied Thermal Engineering)
Despite the omnipresence of household refrigeration appliances, there is still a lack of knowledge about their agerelated efficiency loss over time. Past studies provide basic evidence for increasing electricity consumption of cooling appliances with ageing but fail to investigate the associated technical wear. Concentrating on the degradation of the thermal insulation, we first determined the ageing process of sealed samples of polyurethane rigid foam by investigating changes in cell gas composition and thermal conductivity over time. Simultaneously, the main challenge was to develop an approach that investigates the age-related efficiency loss of the insulation without its destruction. This testing procedure is referred to as the Bonn method. The non-destructive Bonn method was applied to varying refrigerator models in a series of successive experiments to evaluate the insulation degradation over time. Subsequently, the physical relationship between the test value of the Bonn method and the heat transfer through the multi-layered compartment walls of domestic refrigeration appliances was established, ultimately characterising the degrading insulation in terms of increasing heat transfer. Our results give substantiated evidence that the efficiency loss of cooling appliances is greatly influenced by insulation degradation over time. The ageing of sealed samples of polyurethane rigid foam indicates a large initial increase of thermal conductivity by 15% within the first year, corresponding to a change in cell gas composition. These results are in line with those of the Bonn method, emphasising an increasing heat flow through the multi-layered compartment walls of domestic refrigerators with ageing. Therewith, the present study is of significance to a wide range of stakeholders and forms the basis for future research.

An overview of the Meteracom Project - Humphreys, David; Berekovic, Mladen; Kallfass, Ingmar; Scheytt, Christoph; Kuerner, Thomas; Jukan, Admela; Schneider, Thomas; Kleine-Ostmann, Thomas; Koch, Martin; Thomae, Reiner (Proc. 43-nd Meeting of the Wireless World Research Forum (WWRF)",)
We overview the 3-year Meteracom project which will provide traceability to the SI for THz communication measurement parameters. The key objectives are to develop new metrological methods to characterize the measurement systems, system components and propagation channels. The final objective is to develop metrology for functionality and signal integrity of THz communication systems; particularly device discovery and beam tracking, determination of physical layer parameters for digital transmission and real-time performance evaluation.

Time and Age Trends in Free Sugar Intake from Food Groups among Children and Adolescents between 1985 and 2016 - Perrar, Ines; Schadow, Alena M.; Schmitting, Sarah; Buyken, Anette; Alexy, Ute (Nutrients)
Trend analyses suggest that free sugar (FS) intake—while still exceeding 10%E—has decreased among German children and adolescents since 2005, yet that intakes may shift from sugars naturally occurring in foods to added sugars as children age. Thus, we analysed time and age trends in FS intake (%E) from food groups among 3–18 year-olds (1985–2016) using 10,761 3-day dietary records from 1312 DONALD participants (660 boys, 652 girls) by use of polynomial mixed-effects regression models. Among girls, FS from sugar & sweets decreased from 1985 to 2016 (linear trend p < 0.0001), but not among boys (p > 0.05). In the total sample, FS intake from juices increased until 2000 and decreased since 2005 (linear, quadratic trend p < 0.0001). FS from sugar sweetened beverages (SSB) decreased non-linearly from 1985 to 2016 (girls: linear, quadratic, cubic trend p < 0.0001; boys: linear, quadratic, cubic trend p < 0.02). Younger children consumed more FS from juices than older ones, who had a higher FS intake from SSB. FS intake from sugar & sweets increased until early adolescence and decreased afterwards. Since sugar & sweets represent the main source of FS intake and the source with the least pronounced decline in intake, public health measures should focus on these products.

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game

On the impact of probabilistic weather data on the economically optimal design of renewable energy systems – a case study on La Gomera island - Meschede, Henning; Hesselbach, Jens; Child, Michael; Breyer, Christian (International Journal of Sustainable Energy Planning and Management)
Renewable energy and storage systems are widely discussed to minimise the impact of global warming. In addition to the temporal resolution of simulation tools, also the chosen input data might have a strong impact on the performance of renewable energy systems, and energy storage systems in particular. This study analyses the impact of probabilistic weather data on the design of renewable energy systems. The main objective is hereby the determination of the robustness of a recently state-of-the-art design process of a 100% renewable energy and storage system with varying probabilistic input data. The island of La Gomera, Canary Islands, is taken as a case study. Although all analysed systems show some variance in their results, the combination of vehicle-to-grid and power-to-hydrogen shows the best economic performance. Hereby, small island energy systems depending heavily on wind energy show higher variations than those with high shares of solar energy. This analysis illustrates clearly that the choice of one historical reference year is not suitable to determine the expected performance of an energy system. To learn about their sensitivity, synthetic probabilistic inputs as applied in this study are a good way to determine both the expected mean values and their variance.

Gift Purchases as Catalysts for Strengthening Customer–Brand Relationships - Eggert, Andreas; Steinhoff, Lena; Witte, Carina (Journal of Marketing)
Gift giving is an effective means to strengthen interpersonal relationships; it also may initiate and enhance customer–brand relationships. Through a field study conducted with an international monobrand retailer of beauty products, a combination of propensity score matching with difference-in-differences estimations, and two experimental scenario studies, this research demonstrates that gift buyers spend 63% more in the year following a gift purchase than a matched sample of customers who purchase for their personal use. Specifically, gift buyers increase their purchase frequency (25%), spend more per shopping trip (41%), and engage in more cross-buying (49%). The sales lift is particularly pronounced among new customers. Identity theory suggests customer gratitude and public commitment as mediating mechanisms. Gift purchase design characteristics (i.e., assistance during gift purchase and branded gift wrapping) influence the strength of the mediating mechanisms.
Keywords: Marketing; Business and International Management

Time and age trends in morning and evening protein intakes of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Herder, Christian; Buyken, Anette; Alexy, Ute (Journal of Nutritional Science)
Abstract The present study describes time and age trends in morning and evening protein intakes and sources among German children and adolescents from 1985 to 2014. A total of 9757 three-day weighed dietary records of 1246 3- to 18-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were analysed using polynomial mixed-effects regression models. Morning protein intake increased over the study period by approximately 1 % of morning energy intake (linear trend P < 0·0001), with the youngest and the oldest children having the highest protein intake (linear, quadratic trend P < 0·0001). Evening protein intake increased over time by approximately 2 % of evening energy intake in girls (linear trend P < 0·0001) and 1 % of evening energy intake in boys (quadratic trend P = 0·0313), with decreasing intake with age (girls: linear trend P < 0·0001; boys: linear trend P = 0·0963). Time trends were largely due to increases in protein from ‘starchy foods’. In conclusion, morning and evening protein intakes increased modestly between 1985 and 2014; these increases were, however, not accompanied by increases in traditional protein sources (i.e. meat or dairy products).

Towards a Computational Model of Child Gesture-Speech Production - Abramov, Olga; Kopp, Stefan; Nemeth, Anne; Kern, Friederike; Mertens, Ulrich; Rohlfing, Katharina (KOGWIS2018: Computational Approaches to Cognitive Science)
Previous work by [1] studied gesture-speech interaction in adults. [1] focussed on temporal and semantic coordination of gesture and speech and found that while adult speech is mostly coordinated (or redundant) with gestures, semantic coordination increases the temporal synchrony. These observations do not necessarily hold for children (in particular with respect to iconic gestures, see [2]), where the speech and gesture systems are still under development. We studied the semantic and temporal coordination of speech and gesture in 4-year old children using a corpus of 40 children producing action descriptions in task oriented dialogues. In particular, we examined what kinds of information are transmitted verbally vs. non-verbally and how they are related. To account for this, we extended the semantic features (SFs) developed in [3] for object descriptions in order to include the semantics of actions. We coded the SFs on the children’s speech and gestures separately using video data. In our presentation, we will focus on the quantitative distribution of SFs across gesture and speech. Our results indicate that speech and gestures of 4-year olds are less integrated than those of the adults, although there is a large variability among the children. We will discuss the results with respect to the cognitive processes (e.g., visual memory, language) underlying children’s abilities at this stage of development. Our work paves the way for the cognitive architecture of speech-gesture interaction in preschoolers which to our knowledge is missing so far.
Keywords: Speech-gesture integration; semantic features

Towards a Computational Model of Child Gesture-Speech Production - Abramov, Olga; Kopp, Stefan; Nemeth, Anne; Kern, Friederike; Mertens, Ulrich; Rohlfing, Katharina (KOGWIS2018: Computational Approaches to Cognitive Science)
Previous work by [1] studied gesture-speech interaction in adults. [1] focussed on temporal and semantic coordination of gesture and speech and found that while adult speech is mostly coordinated (or redundant) with gestures, semantic coordination increases the temporal synchrony. These observations do not necessarily hold for children (in particular with respect to iconic gestures, see [2]), where the speech and gesture systems are still under development. We studied the semantic and temporal coordination of speech and gesture in 4-year old children using a corpus of 40 children producing action descriptions in task oriented dialogues. In particular, we examined what kinds of information are transmitted verbally vs. non-verbally and how they are related. To account for this, we extended the semantic features (SFs) developed in [3] for object descriptions in order to include the semantics of actions. We coded the SFs on the children’s speech and gestures separately using video data. In our presentation, we will focus on the quantitative distribution of SFs across gesture and speech. Our results indicate that speech and gestures of 4-year olds are less integrated than those of the adults, although there is a large variability among the children. We will discuss the results with respect to the cognitive processes (e.g., visual memory, language) underlying children’s abilities at this stage of development. Our work paves the way for the cognitive architecture of speech-gesture interaction in preschoolers which to our knowledge is missing so far.
Keywords: Speech-gesture integration; semantic features

“As a person, I feel I’ve changed pretty immensely”: Sojourners’ aspirations and self-perceived achievements - Müller, Mareike (The Canadian Modern Language Review)
This article explores the interplay between learners’ linguistic and personal objectives as well as evaluations of their achievements in study-abroad contexts, an area that has thus far remained widely unexplored given the prevalence of product-oriented, outcomes-based research. The study draws on the case of one Canadian student of German who studied abroad at a German university for one year. To adopt an emic perspective, the data gained from a learning history questionnaire, semi-structured interviews, and e-journals were analyzed and interpreted within the framework of narrative analysis. The results show not only that learners’ sojourn objectives may be complex, dynamic, and contradictory in nature but also that they need to be examined beyond their face value, as they are entangled with learners’ negotiations of desirable subject positions and attempts to integrate their sojourn experiences, successes, and frustrations in a coherent and positive life narrative.
Keywords: individual differences; learner beliefs; narrative analysis; sojourn objectives and evaluations; study abroad

Human agency at work: An active approach towards expertise development - Goller, Michael
Michael Goller gives a structured overview of the current discourses of human agency in relation to professional learning and development. Based on this discussion, the author develops a theoretical framework including human agency as an individual feature (i. e., a disposition) as well as a set of self-initiated and goal-directed behaviours that are assumed to affect employees’ learning and development (e. g., crafting of new work experiences). He then further specifies this theoretical framework and investigates it empirically in the domain of geriatric care nursing. Based on the findings of the three empirical studies conducted, the author discusses the relevance of human agency for the development of professional expertise of geriatric care nurses. The work received the American Educational Research Association (AERA) Workplace Learning SIG 2017 Dissertation of the Year Award.
Keywords: Workplace learning; Agency; Expertise

Positive Effects of Promoting Physical Activity and Balanced Diets in a Primary School Setting with a High Proportion of Migrant School Children - Weber, Katharina; Spörkel, Olaf; Mertens, Melina; Freese, Alem; Strassburger, Klaus; Kemper, Boris; Bachmann, Clemens; Diehlmann, Knut; Stemper, Theodor; Buyken, Anette; Ketelhut, Kerstin; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at particular risk for overweight. We assessed the effects of a primary school-based initiative targeted at enhancing physical activity and dietary education among children with a high proportion of migration background. Methods Four 3rd and 4th grade classes (n=70 children, 77% with migration background) participated in a 10-months intervention comprising 2 additional exercise lessons weekly and 10 nutrition lessons per school year. 6 school classes (n=125 children, 65% with migration background) served as control. Before and after the intervention, an assessment of physical fitness and motor skills and questionnaires on dietary behavior and knowledge were conducted. In a subgroup (n=37), after 6 months of the intervention, daily physical activity was assessed by accelerometer-based monitoring. Differences in changes between the groups were assessed using linear regression analyses. Results Changes between the 2 time points for fitness and motor skill tests (differences in standard deviation scores) were larger in the intervention than in the control group for the total mean test value (β=0.38, p<0.001), driven by higher improvements in 5 of the 8 test items, i.e., obstacle race (speed) (β=0.22, p=0.049), standing long jump (strength) (β=0.35, p<0.001), sit-ups (strength) (β=0.33, p=0.002), stand and reach (mobility) (β=0.22, p=0.042), and 6 min run (endurance) (β=0.40, p<0.001), independently of confounders. Changes in dietary knowledge and consumption frequencies did not differ between groups. Conclusions Promoting guided physical activity in a primary school setting with a high proportion of children with migration background positively affected parameters of fitness and motor skills.

How do they find their place? A typology of students' enculturation during the first year at a business school - Jenert, Tobias; Brahm, Taiga; Gommers, Luci; Kühner , Patrizia (Learning, Culture and Social Interaction)
Students' experiences of their first year of studying are of prime importance for their further development in Higher Education (HE). Consequently, the first year and the related phenomena of student performance, retention, and dropout have been extensively studied. Research shows that during the first year, the individual student's ability or failure to adapt to the new socio-cultural environment influences his/her academic success. Yet, surprisingly little is known about the actual processes through which students integrate into the socio-cultural context of HE. Applying a socio-cultural approach, our qualitative interview study followed 14 university students through their first year, investigating why some students experience an easier transition into HE compared to others. Our research results in a typology of four transition types characterized by their orientation towards the socio-cultural context of studying.
Keywords: Student transition; Enculturation; Dropout; Retention

Perceived Competence and Incompetence in the First Year of Mathematics Studies: Forms and Situations - Liebendörfer, Michael; Hochmuth, Reinhard (Didactics of Mathematics in Higher Education as a Scientific Discipline - Conference Proceedings)

Interest development during the first year at university: do mathematical beliefs predict interest in mathematics? - Liebendörfer, Michael; Schukajlow, Stanislaw (ZDM)

The European Perception of Greece as an Investment Market in the Nineteenth Century - Schönhärl, Korinna (Business Cycles in Economic Thought: A history)
Introduction It is not only Greece’s present financial problems and its trouble to attract foreign investors that encourage the research of the past of this chapter of financial history. In addition, Greece’s past provides an inspiring case study that illuminates bankers’ investment decisions in crisis-ridden markets. After its Struggle for Independence from 1821 onward, Greece became a nation state in its own right in the year 1830, independent from the Ottoman Empire (Zelepos, 2014, 37-53). In the preceding Ottoman time there was no foreign investment in the area at all. However by the brink of the Balkan wars in 1911-1912, Greece was perceived by foreign investors as a well-established investment market for state loans as well as private investment in various sectors of trade and industry. How was this process driven forward in spite of the three financial breakdowns that occurred during this period (1825, 1843 and 1893)? How were the ups and downs of the Greek economy perceived and interpreted from abroad? The aim of this chapter is to show interconnections between financial, political and cultural history concerning the development of foreign investment in Greece.

Six-year-olds' perception of home literacy environment and its influence on children's literacy enjoyment, frequency, and early literacy skills - Wiescholek, Sabrina; Hilkenmeier, Johanna; Greiner, Christian; Buhl, Heike M. (Reading Psychology)
Home literacy environment (HLE) makes an important contribution to children's reading acquisition in early years. Even though some research on children's perception exists, children's reports about HLE have been neglected. The present study focuses on N = 281 six-year-old's reports about HLE and its influences on literacy enjoyment, frequency, and early literacy skills. Parents' educational background was expected to predict children-perceived HLE. A positive impact of active HLE on literacy enjoyment and frequency were found. HLE also mediates the relation between parents' background and enjoyment. The importance of children's perspective on HLE regarding family literacy programs is discussed.
Keywords: Linguistics and Language; Developmental and Educational Psychology; Education

The Role of Parents and Peers in the Transition From University to Work Life - Buhl, Heike M.; Noack, Peter; Kracke, Baerbel (Journal of Career Development)
This longitudinal study addresses the role of support given by parents and peers during the transition from university to work life. A sample of 64 German university students in their last year at the university completed scales from the Network of Relationships Inventory regarding general support, namely, instrumental aid and intimacy with mothers, fathers, romantic partners, and friends. Four years later, they assessed domain-specific support when looking for work, namely, joint exploration and instrumental support. Participants perceived receiving both types of support from all significant others. However, joint exploration was more important than instrumental support. They felt especially supported by romantic partners. Women received more support than did men. Both types of domain-specific support were explained by general modes of support assessed 4 years earlier. Whether parents, friends, and partners were perceived as helpful during the transition was explained mainly by joint exploration. Again, support from a partner was seen as especially helpful in contrast to help from parents and friends. The special significance of joint exploration underlines the benefit of counseling at the transition from university to work life.
Keywords: Organizational Behavior and Human Resource Management; General Psychology; Applied Psychology; Education

Children’s Voice in “Nurseries of Democracy“. Participation in Early Childhood Institutions - Klein, Alexandra; Landhäußer, Sandra (Social Work and Society International Online Journal)
According to the UN Conventions on the Rights of the Child all children have a right to participation. This UN Convention has influenced professionals and policy-makers worldwide. Thereby participation in kindergarten refers to children’s possibilities to exercise influence on a range of topics from the rules that are applied in the nursery’s course of a day, the daily program, the interior design of the facility, etc. Which possibilities for participation children actually have in their everyday lives and how they perceive these possibilities has not been sufficiently answered in the international discourse. Based on a standardized survey with 4 and 5 year old children on their experiences with various aspects of participation in pre-school institutions the paper contributes to international childhood and participation research. The empirical findings are related to the democracy-theoretical inspired figures of early childhood institutions as “nurseries of democracy” and broader reflections on social inequalities in early childhood.
Keywords: participation; kindergarten; child’s perspectives; voice; inclusion

In Infants' Hands: Identification of Preverbal Infants at Risk for Primary Language Delay - Lüke, Carina; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf; Ritterfeld, Ute (CHILD DEVELOPMENT)
Early identification of primary language delay is crucial to implement effective prevention programs. Available screening instruments are based on parents' reports and have only insufficient predictive validity. This study employed observational measures of preverbal infants' gestural communication to test its predictive validity for identifying later language delays. Pointing behavior of fifty-nine 12-month-old infants was analyzed and related to their language skills 1 year later. Results confirm predictive validity of preverbal communication for language skills with the hand shape of pointing being superior compared to the underlying motives for pointing (imperative vs. declarative). Twelve-month-olds who pointed only with their open hand but never with their index finger were at risk for primary language delay at 2 years of age.

In Infants' Hands: Identification of Preverbal Infants at Risk for Primary Language Delay - Lüke, Carina; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf; Ritterfeld, Ute (CHILD DEVELOPMENT)
Early identification of primary language delay is crucial to implement effective prevention programs. Available screening instruments are based on parents' reports and have only insufficient predictive validity. This study employed observational measures of preverbal infants' gestural communication to test its predictive validity for identifying later language delays. Pointing behavior of fifty-nine 12-month-old infants was analyzed and related to their language skills 1 year later. Results confirm predictive validity of preverbal communication for language skills with the hand shape of pointing being superior compared to the underlying motives for pointing (imperative vs. declarative). Twelve-month-olds who pointed only with their open hand but never with their index finger were at risk for primary language delay at 2 years of age.

Fake News Is Not Just The Word Of The Year, But A Danger To Democracy That Can Only Be Overcome By Adequate Legal And Media Reforms - Fuchs, Christian (Huffington Post)

Conceptualizations, images, and evaluations of culture in study abroad students - Müller, Mareike; Schmenk, Barbara (Canadian Journal of Applied Linguistics)
This article focuses on the cultural dimension of sojourners’ learning during study abroad periods. By examining the cases of two Canadian learners of German who studied abroad in Germany for 1 year, we aim to amend discussions in existing research on what kind of cultural learning may take place during study abroad and how cultural learning may be conceptualized and operationalized. Our results suggest that assuming that study abroad leads to a heightened intercultural sensitivity, to more cultural knowledge, and to an increased intercultural competence, is problematic with respect to the conceptual underpinnings of “cultural learning.” The notions of culture that underlie much of what participants consider “cultural learning and experience” often remain essentialist. We therefore propose to replace the interculturality paradigm by a transculturality paradigm as it allows us to capture the complexities of study abroad and cultural learning more accurately.

Changes in water and sugar-containing beverage consumption and body weight outcomes in children - Muckelbauer, Rebecca; Gortmaker, Steven L.; Libuda, Lars; Kersting, Mathilde; Clausen, Kerstin; Adelberger, Bettina; Müller-Nordhorn, Jacqueline (British Journal of Nutrition)
Abstract An intervention study showed that promoting water consumption in schoolchildren prevented overweight, but a mechanism linking water consumption to overweight was not substantiated. We investigated whether increased water consumption replaced sugar-containing beverages and whether changes in water or sugar-containing beverages influenced body weight outcomes. In a secondary analysis of the intervention study in Germany, we analysed combined longitudinal data from the intervention and control groups. Body weight and height were measured and beverage consumption was self-reported by a 24-h recall questionnaire at the beginning and end of the school year 2006/2007. The effect of a change in water consumption on change in sugar-containing beverage (soft drinks and juices) consumption, change in BMI (kg/m 2 ) and prevalence of overweight and obesity at follow-up was analysed using regression analyses. Of 3220 enroled children, 1987 children (mean age 8·3 ( sd 0·7) years) from thirty-two schools were analysed. Increased water consumption by 1 glass/d was associated with a reduced consumption of sugar-containing beverages by 0·12 glasses/d (95 % CI −0·16, −0·08) but was not associated with changes in BMI ( P =0·63). Increased consumption of sugar-containing beverages by 1 glass/d was associated with an increased BMI by 0·02 (95 % CI 0·00, 0·03) kg/m 2 and increased prevalence of obesity (OR 1·22; 95 % CI 1·04, 1·44) but not with overweight ( P =0·83). In conclusion, an increase in water consumption can replace sugar-containing beverages. As sugar-containing beverages were associated with weight gain, this replacement might explain the prevention of obesity through the promotion of water consumption.

Eigenkapitalverzehr und Substanzbesteuerung deutscher Unternehmen durch eine Vermögensteuer – eine empirische Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Stichprobe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen, deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300 % der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; Ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

The Impact of Communication Patterns on Distributed Self-Adjusting Binary Search Tree - Strothmann, Thim Frederik (Journal of Graph Algorithms and Applications)
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm that is closely related to the over thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided. To do so, the process of self-adjustment is modeled similarly to a basic network creation game in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and that convergence is related to certain structures of the communication interests, which we call conflicts. We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well. Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.

The crucial first year: a longitudinal study of students’ motivational development at a Swiss Business School - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Higher Education)
In Switzerland, every student graduating from grammar school can begin to study at a university. This leads to high dropout rates. Although students’ motivation is considered a strong predictor of performance, the development of motivation during students’ transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present longitudinal study addresses this research gap and examines the development of economics and management students’ study motivation. It encompasses four waves of data collected throughout the first year, using quantitative online surveys. In total, the sample consists of 820 students. Data is analysed using latent change modelling. Results indicate that students start at a higher level of intrinsic motivation compared to extrinsic motivation. The variability of the starting value of the two constructs is also differing. The analysis also shows a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline.
Keywords: Transition to higher education; Motivation; Longitudinal study; Socio-cultural factors; Latent change model; Switzerland

A typology of students’ enculturation during the first year at University - Jenert, Tobias; Brahm, Taiga; Gommers, Luci; Kühner, Patrizia
The first year of studying has been extensively researched in order to better understand the transition into Higher Education (HE) as well as the phenomena of student performance, retention, and drop out. Although research points to the importance of the socio-cultural dimension of first-year experiences, surprisingly little is known about the actual processes through which students integrate into the socio-cultural context of HE. To address this research gap, an interview study was conducted with 15 first-year university students. The analysis revealed distinctive transition processes into HE that were developed into a typology with four transition types. Interestingly, students who tended to be more critically reflective about their studies were in danger of having a rougher transition than less critically reflective counterparts. For the former, it is essential to develop social relationships that tie them to their studies while the latter manage study-related challenges by simply working through them.

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study - Harris, Carla; Flexeder, Claudia; Thiering, Elisabeth; Buyken, Anette; Berdel, Dietrich; Koletzko, Sibylle; Bauer, Carl-Peter; Brüske, Irene; Koletzko, Berthold; Standl, Marie (BMC Public Health)
Background Understanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour. Methods Dietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. Intakes of 17 food groups, macronutrients and antioxidant vitamins, were described by a) paired Wilcoxon rank sum tests, comparing average intakes at each time-point, and b) Cohen’s kappa “tracking” coefficients, measuring stability of intakes (maintenance of relative tertile positions across time). Further, associations of changes (tertile position increase or decrease vs. tracking) with parental education, family income, child education, pubertal onset, BMI, and screen-time, were assessed by logistic regression and multinomial logistic regression models stratified by baseline intake tertile. Results Both sexes increased average intakes of water and decreased starchy vegetables, margarine and dairy. Females decreased meat and retinol intakes and increased vegetables, grains, oils and tea. Males decreased fruit and carbohydrates and increased average intakes of meat, caloric drinks, water, protein, fat, polyunsaturated fatty acids (PUFAs), vitamin C and alpha-tocopherol. Both sexes presented mainly “fair” tracking levels [κw = 0.21–0.40]. Females with high (vs. low) parental education were more likely to increase their nut intake [OR = 3.8; 95 % CI = (1.7;8.8)], and less likely to decrease vitamin C intakes [0.2 (0.1;0.5)], while males were less likely to increase egg consumption [0.2 (0.1;0.5)] and n3 PUFAs [0.2 (0.1;0.5)]. Females with a higher (vs. low) family income were more likely to maintain medium wholegrain intakes [0.2 (0.1;0.7) for decrease vs. tracking, and 0.1 (0.0;0.5) for increase vs. tracking], and were less likely to decrease vitamin C intakes [0.2 (0.1;0.6)]. Males with high education were less likely to increase sugar-sweetened foods [0.1 (0.1;0.4)]. Finally, BMI in females was negatively associated with decreasing protein intakes [0.7 (0.6;0.9)]. In males BMI was positively associated with increasing margarine [1.4 (1.1;1.6)] and vitamin C intakes [1.4 (1.1;1.6)], and negatively associated with increasing n3 PUFA. Conclusions Average dietary intakes changed significantly, despite fair tracking levels, suggesting the presence of trends in dietary behaviour during puberty. Family income and parental education predominantly influenced intake changes. Our results support the rationale for dietary interventions targeting children, and suggest that sex-specific subpopulations, e.g. low socio-economic status, should be considered for added impact.
Keywords: Puberty; Dietary intake; Dietary changes; Tracking; Determinants; Epidemiology

The impact of communication patterns on distributed locally self-adjusting binary search trees - Strothmann, Thim Frederik (Proceedings of the 9th International Workshop on Algorithms and Computation (WALCOM))
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm, which is closely related to the nearly thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided.To do so, the process of self-adjustment is modeled similarly to a basic network creation game, in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and convergence is related to certain structures of the communication interests, which we call conflicts.We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well.Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.

Hypoplastic left heart in the 6500-year-old Detmold Child - Haas, Nikolaus; Zelle, Michael; Rosendahl, Wilfried; Zink, Albert; Preuss, Rainer; Laser, Kai; Gostner, Paul; Arens, Stephan; Domik, Gitta; Burchert, Wolfgang (Lancet (London, England))

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari
Starting with this issue, the ZFHE will publish one English-speaking edition per year on a topic of international interest, in order to disseminate German-language research results beyond our borders and to encourage discussion in an international context. This first English-language edition focuses on the experiences and the academic socialization of first-year university students. The articles offer both diagnoses and differentiations in terms of different types of first-year students, as well as highlighting their experiences and development during their introduction to the academic environment and examining connections between their academic development and the existing educational environment.

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

How Do They Find Their Place? A Longitudinal Study of Management Students' Attitudes and Motivations During Their First Year at Business School - Jenert, Tobias; Brahm, Taiga
The first year of studying has been extensively researched applying different theoretical lenses to better understand the transition into Higher Education (HE). It is of particular interest to investigate how students deal with frictions between themselves as individuals and what they perceive to be dominant features of the first-year culture of their studies. To tackle this question, a qualitative longitudinal study was conducted. Based on a sociocultural understanding of attitudes and motivations, its aim was to closely follow a relatively small but highly diverse sample of students throughout their first year at a business school in order to develop an in-depth understanding of each individual’s motivational and attitudinal development.
Keywords: Enculturation; first-year students; beginning students; retention; drop-out

The crucial first year: Students’ motivation at a Swiss Business School--a longitudinal study - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Academy of Management Proceedings)
Despite students’ motivation being considered a strong predictor of performance, the development of motivation of business school students has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. This is surprising, as the transition from school to university is a crucial phase in the academic career and can be overwhelming for some students. The present study addresses this research gap and examines the development of economics and management students’ study motivation. The longitudinal study included four waves of data collected throughout the first year using quantitative surveys. Regarding students’ development over time, the analysis showed a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline

Vermögensteuer und ihre Implikationen für den Wirtschaftsstandort Deutschland - eine betriebswirtschaftliche Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Unternehmensgruppe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300% der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

Adherence to the Dutch dietary guidelines is inversely associated with 20-year mortality in a large prospective cohort study - van Lee, L; Geelen, A; Kiefte-de Jong, J C; Witteman, J C M; Hofman, A; Vonk, N; Jankovic, N; Hooft van Huysduynen, E J C; de Vries, J H M; van 't Veer, P; Franco, O H; Feskens, E J M (European Journal of Clinical Nutrition)

The crucial first year: The development of students' motivation at a Business School-a Mixed Methods Study - Brahm, Taiga; Jenert, Tobias
The transition from school to university can be overwhelming for some students. While students' motivation is considered a strong predictor of performance, the development of motivation during students' transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present mixed methods study addresses this research gap and examines the development of economics students' study motivation. The longitudinal mixed-method study included three waves of data collected using quantitative surveys and a series of five interviews conducted with 14 first-year students over eight months. Regarding students' development over time, the quantitative analysis showed a gradual decline in students' motivation. However, in the interviews, certain events during the first year were identified as critical incidents demotivating students. These insights into the development of students' motivation at a business school show that concrete incidents influence students' motivational development; thus, they could be transformed by structural changes.
Keywords: motivation; business school; higher education; latent growth curve model; longitudinal study; mixed methods; interview; students

Transition within higher education institutions (HEI): Differences in learning culture (LC) between first-year, bachelor, and master students at a business school - Gebhardt, Anja; Jenert, Tobias
Tertiary education comprises at least two phases, undergraduate and graduate studies. Often, the first year is regarded another, crucial phase where students familiarize with the study environment. It can be hypothesized that students' individual perceptions of learning and studying as well as the pedagogies they experience differ depending on their current study phase. Yet, differences between the phases in HE have rarely been investigated. To capture differences in student experiences in HE comprehensively, Jenert and Gebhardt (2010) have developed a framework describing Learning Culture in HEI. LC comprises a number of constructs on the three levels of the individual student, pedagogical interactions and the organization. The study first aims to quantitatively describe differences in LC between the phases of HE within a university. Based on this analysis, a second goal is to develop a deeper understanding of how students manage the transitions between different phases by applying qualitative research methods.
Keywords: Higher Education; Transitions; Bachelor; Master

A MINLP Approach for Planning the Renewal of Pipes in Drinking Water Networks - Stapel, Florian; Suhl, Leena
This article presents a novel Mixed Integer Nonlinear Programming (MINLP) approach for ﬁnding a renewal plan of pipes in a water distribution system. We formulate a MINLP model for ﬁnding the times of renewal and suited measurements of pipe dimensions in a multi-year planning horizon. The model includes a multi-period hydraulic simulation of the distribution systems behaviour thereby respecting the friction caused headloss as a nonlinear constraint. We apply the MINLP solver Bonmin to a test network and present ﬁrst numerical results. The models embedding into a general solution framework for water network problems consisting of network reduction and simulation steps in an interated way, is beign discussed. This latter discussion corresponds well to the recent results by C. Hallmann for the problem of tank planning within the mentioned solution framework that has been presented there for the ﬁrst time.

Self-determination and interest development of first-year mathematics students - Liebendörfer, Michael (Oberwolfach Reports)

Risk Reduction in Natural Disaster Management Through Information Systems: A Literature review and an IS design science research agenda - Schryen, Guido; Wex, Felix (International Journal of Information Systems for Crisis Response and Management (IJISCRAM))
Natural disasters, including earthquakes, Tsunamis, floods, hurricanes, and volcanic eruptions, have caused tremendous harm and continue to threaten millions of humans and various infrastructure capabilities each year. In their efforts to take countermeasures against the threats posed by future natural disasters, the United Nations formulated the ?Hyogo Framework for Action?, which aims at assessing and reducing risk. This framework and a global review of disaster reduction initiatives of the United Nations acknowledge the need for information systems research contributions in addressing major challenges of natural disaster management. In this paper, we provide a review of the literature with regard to how information systems research has addressed risk assessment and reduction in natural disaster management. Based on the review we identify research gaps that are centered around the need for acquiring general knowledge on how to design IS artifacts for risk assessment and reduction. In order to close these gaps in further research, we develop a research agenda that follows the IS design science paradigm.
Keywords: Natural Disaster Management; Risk Reduction; Hyogo Framework; IS Design Science; Literature review

Carbohydrate quality is not associated with liver enzyme activity and plasma TAG and HDL concentrations over 5 years in an older population - Goletzke, Janina; Buyken, Anette; Gopinath, Bamini; Rochtchina, Elena; Barclay, Alan W.; Cheng, Guo; Brand-Miller, Jennie C.; Mitchell, Paul (British Journal of Nutrition)
Non-alcoholic fatty liver disease (NAFLD) is closely associated with insulin resistance and obesity. Hence, carbohydrate quality could be of relevance to the risk of NAFLD, but prospective data are lacking. The aim of the present study was to investigate longitudinal associations between carbohydrate quality (including dietary glycaemic index (GI) and intakes of sugar, starch and fibre) and markers of liver function in an older Australian population. The analysis was based on 866 participants ( ≥ 49 years) of the Blue Mountains Eye Study with fasting blood specimens and dietary intake data at baseline and 5-year follow-up. Multi-level mixed regression analysis was used to relate dietary GI and sugar, starch and fibre intake to the liver enzymes alanine aminotransferase (ALT) and γ-glutamyltransferase (GGT), as well as fasting TAG and HDL-cholesterol (HDL-C). After adjustment for potential confounding factors, a lower fibre intake was cross-sectionally related to higher GGT ( P = 0·02) and fasting TAG ( P = 0·002) levels, with fruit fibre being the most relevant fibre source ( P = 0·095 for GGT; P = 0·003 for TAG). A higher dietary GI was associated with lower HDL-C ( P = 0·046). Changes in carbohydrate quality during 5 years were not related to changes in ALT, GGT, TAG or HDL-C ( P ≥ 0·08). In conclusion, the absence of longitudinal associations between carbohydrate quality and liver enzymes and serum lipids in this older population does not support a major role of carbohydrate nutrition in liver function among the elderly.

Time trends in dietary fat intake in a sample of German children and adolescents between 2000 and 2010: not quantity, but quality is the issue - Libuda, Lars; Alexy, Ute; Kersting, Mathilde (British Journal of Nutrition)
Dietary fat intake in childhood may influence the risk for developing chronic diseases. The objective of the present study was to examine secular trends in the parameters of fat intake between 2000 and 2010 in a sample of German children and adolescents ( n 808) participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Dietary data from 4380 3 d weighed dietary records were analysed using repeated-measures regression to determine time trends in fat quantity, i.e. the intake of total fat, and in fat quality, i.e. the ratios of SFA, MUFA and PUFA. In young children (2–3 years) and in adolescents (13–18 years), total fat intake remained stable over time, but decreased by 0·08 % of total energy (%E) per year in 4–12-year-old children. In 2010, median fat intake was at the upper end of the recommendations. SFA intake decreased slightly in 2–3- and 4–12-year-old children by 0·09 and 0·05 %E per year, respectively. MUFA and PUFA intakes remained stable in all the age groups except in adolescents. Here, PUFA intake decreased initially, but increased between 2005 and 2010. In 2010, only between 3 and 18 % of the respective age groups had an intake of SFA or PUFA within the recommendations. In conclusion, fat quantity and quality did not change substantially between 2000 and 2010. Fat quality, in particular, needs to be improved, since a large percentage of our sample did not meet the recommended intakes for SFA and PUFA.

How Business Students Attitudes towards their University and Studying Develop during the First Year: A Qualitative Longitudinal Study - Jenert, Tobias; Brahm, Taiga
The aim of this qualitative study is first to investigate the attitude development of students in their initial year at university. College effectiveness research has shown that attitudes towards studying as well as to one's university are key factors influencing student engagement. Up to now, little is known about the processes through which such attitudes develop. Based on the theory of planned behaviour (Ajzen & Fishbein, 1980), the study addresses this research gap in three parts: a) development paths of students' attitudes towards studying and the university; b) the normative behaviour of the fellow students as well as significant persons, c) university-related experiences during the first year influencing students' attitude development. To answer these research questions, a series of five interviews was conducted throughout the first year with a total of 13 first-year students at the University of St. Gallen/Switzerland. Data analysis was performed referring to the procedures suggested by Neale (2012) for qualitative longitudinal data. To master the challenge of displaying developments over time, graphical analysis was used to construct a case history (cf. Henderson, Holland et al., 2012) for each individual. Regarding the students' developments over time, the analysis shows the participants' attitudes towards the university became more differentiated over time. A second major result concerns frictions between students' own attitudes and what they perceive to be the dominant normative behaviour. It became obvious that this developmental process is influenced by concrete incidents students experience during the first year and thus, can be shaped by structural changes.
Keywords: student attitudes; qualitative research; longitudinal study; student motivation

A latent growth curve analysis of Business students' intrinsic and extrinsic motivation - Brahm, Taiga; Jenert, Tobias
The proposed paper aims to investigate the longitudinal development of students' motivation over the first year of their studies at a business school by using latent growth curve modeling. The study tackles the following core research questions: How do first-year university students' intrinsic and extrinsic vary over time? Which (motivational) factors are related to students' motivational development? Although motivational dispositions have been analyzed extensively in previous studies, their longitudinal development has hitherto not been examined in the higher education context. This longitudinal study is conducted at the University of St. Gallen in Switzerland. The current sample includes 280 first-year students who have been surveyed three times and who are representative of the first-year student population. Descriptive results show that prior to their studies, students were motivated most by intrinsic factors, however, extrinsic motivation was also quite high. Employing latent growth curve modeling, it could be shown that both intrinsic and extrinsic motivation decline significantly over the course of the first year (8 months). The study contributes to motivation theory by providing further insights into the development of academic motivation over time. Latent growth curve modeling as a method can be well used for longitudinal data analysis, thus, excluding measurement error from longitudinal data. Furthermore, the study supports educational developers by determining factors influencing students' motivational development.
Keywords: motivation; intrinsic motivation; extrinsic motivation; latent growth curve modeling; longitudinal data analysis; ASEQ; higher education; studying

Exploring Intermediate Vocational Education and Training for 16-19 Year-olds in Germany and England - Higham, J. J. S.; Kremer, H.-Hugo; Yeomans, D. (The Architecture of Innovative Apprenticeship)

A story about a word: does narrative presentation promote learning of a spatial preposition in German two-year-olds? - Nachtigäller, Kerstin; Rohlfing, Katharina; McGregor, Karla K. (Journal of Child Language)
We trained forty German-speaking children aged 1;8–2;0 in their comprehension of UNTER [UNDER]. The target word was presented within semantically organized input in the form of a ‘narrative’ to the experimental group and within ‘unconnected speech’ to the control group. We tested children’s learning by asking them to perform an UNDER-relation before, immediately after, and again one day after the training using familiarized and unfamiliarized materials. Compared to controls, the experimental group learned better and retained more. Children with advanced expressive lexicons in particular were aided in generalizing to unfamiliarized materials by the narrative presentation. This study extends our understanding of how narrations scaﬀold young children’s enrichment of nascent word knowledge.

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Sievers, Sönke; Mokwa, Christopher Frederik
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Sievers, Sönke; Mokwa, Christopher Frederik
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Mokwa, Christopher Frederik; Sievers, Sönke (SSRN Electronic Journal)
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Mokwa, Christopher; Sievers, Sönke (SSRN Electronic Journal)
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

Regional and socio-economic differences in food, nutrient and supplement intake in school-age children in Germany: results from the GINIplus and the LISAplus studies - Sausenthaler, Stefanie; Standl, Marie; Buyken, Anette; Rzehak, Peter; Koletzko, Sibylle; Bauer, Carl Peter; Schaaf, Beate; von Berg, Andrea; Berdel, Dietrich; Borte, Michael; Herbarth, Olf; Lehmann, Irina; et al. (Public Health Nutrition)
Abstract Objective To describe regional differences between eastern and western Germany with regard to food, nutrient and supplement intake in 9–12-year-old children, and analyse its association with parental education and equivalent income. Design Data were obtained from the 10-year follow-up of the two prospective birth cohort studies – GINIplus and LISAplus. Data on food consumption and supplement intake were collected using an FFQ, which had been designed for the specific study population. Information on parental educational level and equivalent income was derived from questionnaires. Logistic regression modelling was used to analyse the effect of parental education, equivalent income and region on food intake, after adjusting for potential confounders. Setting Germany. Subjects A total of 3435 children aged 9–12 years. Results Substantial regional differences in food intake were observed between eastern and western Germany. Intakes of bread, butter, eggs, pasta, vegetables/salad and fruit showed a significant direct relationship with the level of parental education after adjusting for potential confounders, whereas intakes of margarine, meat products, pizza, desserts and soft drinks were inversely associated with parental education. Equivalent income had a weaker influence on the child's food intake. Conclusions Nutritional education programmes for school-age children should therefore account for regional differences and parental education.

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela (Modeling and Using Context: 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011, Proceedings)
This paper presents a novel linguistic information extraction approach exploiting analysts’ stock ratings for statistical decision making. Over a period of one year, we gathered German stock analyst reports in order to determine market trends. Our goal is to provide business statistics over time to illustrate market trends for a user-selected company. We therefore recognize named entities within the very short stock analyst reports such as organization names (e.g. BASF, BMW, Ericsson), analyst houses (e.g. Gartner, Citigroup, Goldman Sachs), ratings (e.g. buy, sell, hold, underperform, recommended list) and price estimations by using lexicalized finite-state graphs, so-called local grammars. Then, company names and their acronyms respectively have to be cross-checked against data the analysts provide. Finally, all extracted values are compared and presented into charts with different views depending on the evaluation criteria (e.g. by time line). Thanks to this approach it will be easier and even more comfortable in the future to pay attention to analysts’ buy/sell signals without reading all their reports.

Sound & Image. An experimental study on the influence of acoustical parameters on the perception of a product’s image in TV-commercials - Flath, Beate (Audio Branding Year Book 2010)

Trends in dietary carbohydrate quality during puberty from 1988 to 2007: a cause for concern? - Cheng, Guo; Libuda, Lars; Karaolis-Danckert, Nadina; Alexy, Ute; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (British Journal of Nutrition)
The extent to which the quality of dietary carbohydrates (CHO) changes throughout puberty is not known. We analysed trends in the quantity and quality of CHO intake among German adolescents by separately examining trends during puberty (pubertal trends) and trends in CHO intake from 1988 to 2007 (secular trends). Linear mixed-effects regression analyses were performed in 216 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study who had provided weighed 3 d dietary records at the onset of the pubertal growth spurt (defined by age at take-off) and over the subsequent 4 years. Over the course of puberty, CHO quality changed little: added sugar intake from beverages increased in girls (0·25 ( se 0·12) % energy (% E)/year, P = 0·04) and added sugar intake from sweets decreased in both sexes (boys: − 0·22 ( se 0·11) % E/year, P = 0·049; girls: − 0·20 ( se 0·10) % E/year, P = 0·04). For both sexes, significant upward secular trends were observed for CHO (% E), glycaemic load (g/MJ) and added sugar intakes from sources other than sweets and soft drinks (% E), while absolute fibre intake (g/d) decreased ( P ≤ 0·04). Concomitant increases in total added sugar intake (% E) and decreases in fibre and whole-grain densities (g/MJ) ( P = 0·001–0·02) were confined to boys only. The quality of dietary CHO consumed by healthy German adolescents shows notable secular declines, but does not change markedly during puberty. Public health initiatives should be tailored to improve the overall quality of CHO nutrition.

Type 2 diabetes mellitus and risk of coronary heart disease: results of the 10-year follow-up of the PROCAM study - Buyken, Anette; von Eckardstein, Arnold; Schulte, Helmut; Cullen, Paul; Assmann, Gerd (European Journal of Cardiovascular Prevention & Rehabilitation)

Armed for the spam battle - a technological and organizational infrastructure framework - Schryen, Guido (40th Annual Hawaii International Conference on System Sciences)
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause economic harm to the tune of about several billion US\$ per year. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose here a new infrastructure framework that combines several anti-spam measures in a framework that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits he number of e-mails that can be sent per day and per account. This paper first gives an overview of the framework, then it provides technological and organizational details of the infrastructure, the deployment of which depends to a large degree on its acceptance and propagation by the ICANN, the ISOC, and by large e-mail service providers. Finally, the paper discusses the limitations and drawbacks of the proposed framework.

Well-being and the child-parent relationship at the transition from university to work life - Buhl, Heike M. (Journal of Adolescent Research)
This longitudinal study addresses the impact of the transition from university to work life on emerging adults' well-being and their relationship with their parents. A sample of 102 German students attending their last year at the university (M = 25.44 years, SD = 2.61) completed a questionnaire. Among others, scales from the Network of Relationships Inventory and symptom checklists were administered. Four years later, 51 employed participants of the initial sample were contacted again. During the transition from university to work life, well-being and the relationship with their parents improved. Following a typological approach, two groups of emerging adults were revealed by means of cluster analyses. Well-being in one group increased, whereas well-being in the second group decreased. Group membership was predicted by sex, personality, and the child–parent relationship in university times.

One Year operation of Offshore Metmast Amrumbank West - Bendfeld, Jörg; Splett, Michael; Voss, Jürgen; Higgen, Anne; Krieger, Jens

Optical properties of semiconductor photonic-crystal structures: spatially-inhomogeneous excitonic resonances and optical gain - Meier, Torsten; Reichelt, Matthias; Pasenow, B.; Stroucken, T.; Koch, S.W. (2005 annual conference of the German Physical Society (DPG) during the World year of physics)

Teaching Object-Oriented Concepts with Eclipse - Meyer, Matthias; Wendehals, Lothar (Proc. of the Eclipse Technology eXchange Workshop (ETX), Satellite Event of the 19th Conference on Object-Oriented Programming, Systems, Languages, and Applications (OOPSLA), Vancouver, Canada)
Object-oriented software development is a subject area difficult to teach, espcially to beginners. They face a lot of abstraction and (from a beginners point of view) isolated topics, such as the syntax and semantics of a programming language, the functionality of a software development environment and basic object-oriented concepts. Although many professionals in education believe in the ``object first'' approach as the best method of introducing object-oriented concepts, there is no common agreement on how to start such courses. Current study programs often begin by teaching a programming language, instead of focusing on the basics of object-oriented concepts. In the last years a learning environment was developed based on a visual programming language to abstract away from details. It assists teaching step-by-step object-oriented concepts and the syntax and semantics of a programming language in secondary schools and first year university courses. Our goal is to port this learning environment to the widely used IDE Eclipse.

Storage Management as Means to cope with Exponential Information Growth - Scheideler, Christian; Salzwedel, Kay; Meyer auf der Heide, Friedhelm; Brinkmann, André; Vodisek, Mario; Rückert, Ulrich (Proceedings of SSGRR 2003)
The advances in Internet technology have led to tremendous improvements in business, education, and science and have changed the way we think, live, and communicate. Information exchange has become ubiquitous by the possibilities offered through modern technologies. We are able to offer information 24 hours a day through our web sites and can leave messages every time and from anywhere in the world. This change in communication has led to new challenges. Enterprises have to deal with an information amount that doubles every year. The technological foundation to cope with this information explosion is given by Storage Area Networks (SANs), which are able to connect a great number of storage systems over a fast interconnection network. However, to be able to use the benefits of a SAN, an easy-to-use and efficient management support has to be given to the storage administrator. In this paper, we will suggest new storage management concepts and we will introduce a new management environment that is able to significantly reduce management costs and increases the performance and resource utilization of the given SAN infrastructure.

Players, Playthings and Patterns: Three Stages of Heteronomy in Beckett's Mature Drama - Tönnies, Merle (Samuel Beckett Today / Aujourd'hui: Endlessness in the Year 2000 / Fin sans fin en l'an 2000)